Can Rana Plaza happen again in Bangladesh?. (March 2021) - Barua, Uttama; Wiersma, J.W.F.; Ansary, Mehedi Ahmed
Highlights: Initiatives for structural safety in Bangladesh RMG sector. Factory building assessment initiatives reached the target. Progress in the remediation under National Initiative not up to the mark. Non-cooperation of the factory owners and incomplete list of factories. Challenge to ensure the sustainability of the safety initiatives. Abstract: Workplace safety has been a great concern in the RMG sector in Bangladesh resulting in accidents from-time-to-time. The collapse of Rana Plaza on April 24, 2013, is one of the deadliest industrial disasters in the world. This accident resulted in different diversified national and international initiatives to improve the workplace safety. This paper aims to reveal whether such initiatives could truly ensure structural safety in the sector. The objectives of this research are threefold. Firstly, to review the process of ensuring structural safety; secondly, to review and understand the progress and the way forward in the process; thirdly, to discuss the possibility of any such accidents in the Bangladesh RMG sector. This research has been carried out through a review of relevant literature from different sources. It has found that factory building assessment initiatives have reached the target and the remediation is progressing. But some issues would require further attention. They include unsatisfactory progress in the remediation under National Initiative; non-inclusion of factory buildings due to unwillingness of the factory owners and incomplete list of factories; limited capacity in terms of human resources, technical issues, and database management; error in the activities; fund management and disbursement for remediation; the transition of Remediation Coordination Cell (RCC) with the required capacity to ensure the sustainability; and finally and most importantly lack of cooperation and false information provided by the factory owners during the inspection. If these issues cannot be addressed immediately then undoubtedly, Rana Plaza can happen again in Bangladesh.